Possibilities of physiotherapy in lipodystrophy - Korabiusz, Katarzyna; Fabian-Danielewska, Anna; Wawryków, Agata; Stecko, Monika; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Lipodystrophy is one of the most common and the most undesirable female dermatological conditions. Both slim and overweight people can struggle with it. It is possible to fight cellulite with various physiotherapeutic techniques and methods.Research goal: Goal of this dissertation is a review of literature about possibilities of physiotherapy in lipodystrophy.Conclusion: The appropriate physiotherapeutic methods are necessary to improve the flexibility, appearance and microcirculation in areas affected by lipodystrophy.